Core-shell structure and manufacturing method thereof
Patent Information
- Application Number
- KR1020230190964
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-12-26
- Publication Date
- 2026-09-15
- Estimated Expiration
- 2043-12-26
Smart Images

Figure 112023145297524-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a method for manufacturing a core-shell structure and a core-shell structure manufactured according to the same. A crystalline core-shell structure can be manufactured by a method of photo-sintering only the shell of a core-shell structure by irradiating white light (Intense Pulsed Light, IPL). Background Technology
[0003] Conventional methods for manufacturing core-shell structures using thermal sintering have the problem that it is difficult to suppress side reactions at the interface between the core and shell materials. Furthermore, thermal sintering can affect the structure of the core itself. However, by utilizing photo-sintering with ultraviolet white light (IPL) as proposed in this invention, selective sintering of only the surface layer in the core-shell structure is possible, allowing for the sintering of the surface layer without the issue of side reactions. Additionally, since photo-sintering can be completed within seconds, the effect of reducing process costs can also be achieved. Prior art literature
[0005] Korean Published Patent Application No. 10-2013-0014929, "Method for Electrosintering Metal Nanoparticle Patterns Using Heat Treatment" The problem to be solved
[0006] One objective of the present invention is to selectively sinter only the shell of a core-shell structure through photo-sintering.
[0007] Another objective of the present invention is to reduce time and cost in the process of sintering a core-shell structure.
[0008] Another objective of the present invention is to apply a core-shell structure to an energy storage device. means of solving the problem
[0010] A method for manufacturing a core-shell structure according to the present invention comprises the steps of preparing a core-shell structure and selectively optically sintering the shell by irradiating the core-shell structure with intense pulsed light (IPL) from a light irradiation unit.
[0011] According to one embodiment, in the step of preparing a core-shell structure, the thickness of the shell may be 10 nm to 50 μm.
[0012] According to one embodiment, in the step of selectively photo-sintering the shell, the shell may be selectively crystallized.
[0013] According to one embodiment, in the step of selectively photo-sintering the shell, an interfacial reaction between the core and the shell can be prevented.
[0014] According to one embodiment, the pulse of extreme white light can be maintained for 0.01 seconds to 10 seconds.
[0015] According to one embodiment, the number of pulses of extreme white light may be 1 to 30.
[0016] According to one embodiment, the voltage applied to the light irradiation part may be 100 V to 800 V.
[0017] The core-shell structure according to the present invention is manufactured according to the method for manufacturing a core-shell structure according to the present invention and optionally includes a crystallized shell.
[0018] According to one embodiment, the thickness of the crystallized shell may be 10 nm to 50 μm.
[0019] According to one embodiment, the crystallized shell has an ionic conductivity of 10 -12 S / cm to 10 -7 It can be S / cm.
[0020] According to one embodiment, the core-shell structure may be included in any one selected from an all-solid-state battery, a lithium battery, and a fuel cell. Effects of the invention
[0022] According to an embodiment of the present invention, crystallinity can be expressed by selectively sintering only the shell of a core-shell structure through photo-sintering using IPL.
[0023] According to an embodiment of the present invention, the time and cost of the core-shell structure sintering process can be reduced.
[0024] According to an embodiment of the present invention, a core-shell structure can be applied to various energy storage devices, such as lithium batteries and fuel cells. Brief explanation of the drawing
[0026] Figure 1 is a schematic diagram of an energy storage device using a core-shell structure and a magnified view of a part thereof. FIG. 2a is a TEM (Transmission Electron Microscope) image (left) and an EDS (Energy Dispersive X-ray Spectroscopy) image (right) of a core-shell structure (Comparative Example 1-1) taken at low magnification. FIG. 2b is a TEM (Transmission Electron Microscope) image (left) and an EDS (Energy Dispersive X-ray Spectroscopy) image (right) of a core-shell structure (Comparative Example 1-1) taken at a magnification greater than that of FIG. 2a. FIG. 3a is a high-magnification TEM (transmission electron microscope) image of a core-shell structure (Comparative Example 1-1). FIG. 3b is a high-magnification EDS (energy dispersive X-ray spectroscopy) image of a core-shell structure (Comparative Example 1-1). Figure 4 is an image of one powder of the core-shell structure (Comparative Example 1-1) observed using SEM (Scanning Electron Microscope) and EDS (Energy Dispersive X-ray Spectroscopy). Figure 5a is an HR-TEM image of a photo-sintered core-shell structure (Example 1). FIG. 5b is an image of a photo-sintered core-shell structure (Example 1). Figure 6 shows the results of crystallinity analysis performed on the examples and comparative examples using X-ray diffraction. Figure 7 is a graph showing the charge / discharge capacity measured for the examples and comparative examples. Specific details for implementing the invention
[0027] Embodiments of the present invention will be described in detail below with reference to the attached drawings and the contents described therein, but the present invention is not limited or restricted by the embodiments.
[0028] The terms used herein are for describing the embodiments and are not intended to limit the invention. In this specification, the singular form includes the plural form unless specifically stated otherwise in the text. As used herein, "comprises" and / or "comprising" do not exclude the presence or addition of one or more other components, steps, actions, and / or elements to the mentioned components, steps, actions, and / or elements.
[0029] As used herein, terms such as “examples,” “examples,” “aspects,” “examples,” etc., are not to be interpreted as implying that any described aspect or design is superior or more advantageous than other aspects or designs.
[0030] Furthermore, the term 'or' refers to an inclusive or rather an exclusive or. That is, unless otherwise noted or is not evident from the context, the expression 'x uses a or b' refers to any one of the natural inclusive permutations.
[0031] Additionally, singular expressions (“a” or “an”) used in this specification and claims should generally be interpreted to mean “one or more” unless otherwise stated or it is clear from the context that they relate to the singular form.
[0032] The terms used in the description below have been selected as being common and universal in the relevant technical field, but other terms may exist depending on technological development and / or changes, conventions, preferences of the skilled technician, etc. Therefore, the terms used in the description below should not be understood as limiting the technical concept, but as illustrative terms to explain the embodiments.
[0033] In addition, in specific cases, there are terms arbitrarily selected by the applicant, and in such cases, their detailed meanings will be described in the relevant explanatory section. Therefore, the terms used in the description below must be understood not merely as their names, but based on their meanings and the content throughout the specification.
[0034] In addition, when a part such as a membrane, layer, region, or configuration request is described as being "on" or "on" another part, it includes not only cases where it is directly on top of the other part, but also cases where another membrane, layer, region, or component is interposed in between.
[0035] Unless otherwise defined, all terms used in this specification (including technical and scientific terms) may be used in a meaning that is commonly understood by those skilled in the art to which the present invention pertains. Additionally, terms defined in commonly used dictionaries are not to be interpreted ideally or excessively unless explicitly and specifically defined otherwise.
[0036] Meanwhile, in describing the present invention, if it is determined that a detailed description of related known functions or configurations could unnecessarily obscure the essence of the invention, such detailed description will be omitted. Furthermore, the terminology used in this specification is used to appropriately express embodiments of the present invention, and may vary depending on the intent of the user or operator, or the conventions of the field to which the invention belongs. Accordingly, the definitions of these terms should be based on the content throughout this specification.
[0038] Generally, heat treatment methods using a furnace require the application of high thermal energy for a long period, resulting in high time and cost consumption for the sintering process. Furthermore, in core-shell structures, sintering methods using a furnace can lead to unwanted reactions at the interface where the core and shell meet. Therefore, when the core and shell in a core-shell structure are composed of different materials, it is difficult to impart crystallinity by sintering only the shell. In other words, it is difficult to control the thermal sintering method to express the inherent crystallinity of the shell material by applying thermal energy, while preventing side reactions between the core and shell materials and ensuring that the core material and its structure are not affected.
[0039] To address this, the present invention aims to sinter a core-shell structure using a photonic sintering method. Unlike thermal sintering, the photonic sintering method allows for rapid raising or lowering of the target material temperature and enables partial sintering of the area irradiated with light, thereby saving process time and costs. Furthermore, since it is possible to sinter only the shell without affecting the core, it is particularly suitable for sintering core-shell structures.
[0040] Meanwhile, the wavelength range of light absorbed by a material varies depending on the color it exhibits. Among these, white light is light that includes the entire visible light range, so when using white light, especially intense pulsed light (IPL), for photo-sintering, it has the advantage of being universally applicable without limitations on the type of material to be photo-sintered.
[0042] A method for manufacturing a crystalline core-shell structure according to the present invention comprises the step of preparing a core-shell structure (S100) and the step of selectively photo-sintering the shell by irradiating the structure with intense pulsed light (IPL) from a light irradiation unit (S200).
[0043] In the step (S100) of preparing the core-shell structure, the type of material used as the core and the type of material used as the shell can be prepared differently.
[0044] At this time, the material constituting the core (hereinafter referred to as the core material) may include one or more selected from the group consisting of metals and metal oxides. As metals, one or more selected from platinum, nickel, lithium, manganese, and cobalt may be used, but are not limited thereto. As metal oxides, one or more selected from zirconia (zirconium oxide), ceria (cerium oxide), and lanthanum-based perovskites may be used, but are not limited thereto.
[0046] Meanwhile, the material constituting the shell (hereinafter referred to as the shell material) may be one or more selected from the group consisting of metals and metal oxides. In this case, one or more selected from platinum, nickel, lithium, manganese, and cobalt may be used as the metal, but are not limited thereto. In addition, one or more selected from zirconia, ceria, alumina, and lanthanum-based perovskites may be used as the metal oxide, but are not limited thereto.
[0047] In other words, any material that can be used as a core can also be used as a shell material. However, different materials are used for the core and shell materials that constitute the core-shell structure.
[0048] Since the shell is used to suppress phase transformation of the core material or to suppress side reactions at the interface between heterogeneous materials (core material and shell material), it can preferably take the form of a thin film covering the surface of the core, and it is preferable to use chemically stable materials such as zirconia, ceria, or alumina.
[0050] Core-shell structures can be utilized in energy storage devices, including all-solid-state batteries, lithium batteries, and fuel cells. In all-solid-state batteries and lithium batteries, core-shell structures can be used as cathode materials.
[0052] Figure 1 is a schematic diagram showing an enlarged portion of an energy storage device in which a core-shell structure is used. The energy storage device may be various types of batteries, including all-solid-state batteries, lithium batteries, and fuel cells. In Figure 1, the gray plate represents the substrate constituting the electrode, the blue sphere represents the cathode material constituting the anode, the orange sphere represents the electrolyte, the green sphere represents the cathode material constituting the anode, and the black sphere represents a material added to ensure superior electrical conductivity in the battery. The cathode material is composed of a core-shell structure. The part indicated in blue is the shell, and although the core is not illustrated, it is located inside the shell.
[0054] In the step (S200) of light-sintering the shell by irradiating the structure with ultraviolet white light (IPL) in the light irradiation unit, a xenon lamp, a halogen lamp, etc., can be used as the light irradiation unit.
[0055] Because extreme white light performs photo-sintering by locally concentrating energy in a very short time of milliseconds (ms), it is possible to selectively photo-sinter only the shell in a core-shell structure.
[0056] When extreme frequency white light is applied to a shell, the light energy is converted into thermal energy from the surface of the shell in the depth direction through the vibration of the particles constituting the shell, and the crystallinity of the shell can be manifested due to the heating effect of the converted thermal energy.
[0057] As temperature rises, constituent materials acquire thermal energy and form a more stable phase. Unlike liquids or gases, the atomic arrangement in solids is not free but fixed, forming specific crystal structures such as simple cubic (SC), body-centered cubic (BCC), and face-centered cubic (FCC); these crystal structures can be determined by the size of the atoms present. Furthermore, when multiple substances are mixed together rather than as a single material, atoms can shift according to the solid's crystal structure based on their atomic size. This process is carried out through the application of thermal energy.
[0059] Since the core-shell structure included in all-solid-state batteries and lithium batteries is a material constituting the electrode, it must possess excellent ionic or electrical conductivity. To this end, the core-shell structure may include a photo-sintering process during fabrication, and can be realized as a morphologically stable circular shape during the photo-sintering process.
[0061] In the present invention, to selectively sinter only the shell, the irradiation conditions of extreme frequency white light are controlled so that when thermal energy converted from the shell to the core direction (depth direction) is transferred, thermal energy is prevented from being transferred to the core. Although the selective sintering of the shell may be due to differences in the degree of sintering resulting from the difference in the materials constituting the core and the shell, the present invention aims to control the light irradiation process so that heat is not transferred to the interface between the two materials.
[0062] Furthermore, sintering by light absorption is completed within a very short time, and since the amount of transferable energy decreases as the thickness of the material to be sintered increases, the conditions of the shell can be controlled to prevent energy from being transferred to the interface between the core and the shell. This prevents unwanted side reactions from occurring at the interface.
[0064] According to one embodiment, in the step of preparing a core-shell structure, the thickness of the shell may be 10 nm to 50 μm. Preferably, the thickness of the shell may be 10 nm to 1 μm. More preferably, the thickness of the shell may be 14 nm to 16 nm. If the thickness of the shell is too thin, light energy may be transferred to the core during photo-sintering, and if the thickness of the shell is too thick, the sintering of the shell may proceed unevenly.
[0065] The thickness of the shell can be manufactured differently depending on the deposition method. For example, shells produced using atomic-scale chemical vapor deposition, such as atomic film deposition, can be formed at the nanoscale. However, deposition methods using liquid-phase chemical deposition or sol-gel processes tend to result in somewhat thicker shells ranging from hundreds of nanometers to several micrometers.
[0066] Generally, in core-shell structures, the shell is significantly thin in the nanometer (nm) to micrometer (μm) range, so when thermal sintering is performed instead of photo-sintering, the core and shell are sintered together, and side reactions at the interface inevitably occur.
[0068] According to one embodiment, in the step of selectively photo-sintering the shell, the shell may be selectively crystallized.
[0069] In this specification, "crystallization" refers to a substance having a specific shape and size at the atomic level when existing in a solid state. In other words, crystallization is defined as the formation of a specific crystal structure in a solid, and crystallization leads to the induction of crystalline properties. Conversely, a solid that does not possess a specific crystal structure is referred to as amorphous. The phenomenon of crystallization can generally be confirmed using X-ray diffraction analysis, which analyzes the information obtained from X-rays diffracted at specific angles.
[0070] Crystallized materials possess crystallinity, which can lead to changes in functional properties along with changes in physical properties. For example, zirconia- or ceria-based metal oxides can exhibit ionic conductivity through crystallization. That is, when a crystal structure is formed, atomic vacancies are created by defects in the material, and ions can move along these vacancies, thereby manifesting ionic conductivity. Furthermore, while metals are generally electrically conductive materials, metal oxides do not. However, if a material possesses a specific crystal structure called a perovskite structure, it can exhibit electrical conductivity despite being an oxide. Therefore, the development of crystallinity is essential to enable electrical conductivity in oxide materials.
[0072] According to one embodiment, in the step of selectively photo-sintering the shell, an interfacial reaction between the core and the shell can be prevented.
[0073] When different materials are used to constitute the core and shell in a core-shell structure, chemical reactions occurring at the interface between the two materials may lead to unwanted material or phase changes at the interface. Due to such generated materials or phases, the function of the core or shell may be degraded or lost. Therefore, when the core-shell structure is photo-sintered, interfacial reactions between the core and the shell can be suppressed.
[0075] According to one embodiment, a pulse of extreme white light may be maintained for 0.01 seconds to 10 seconds. In this specification, "pulse" means a series of waves that exist for only a short period of time, and the time during which the pulse is maintained means the time during which extreme white light is applied per pulse.
[0076] If the pulse of the extreme white light is less than 0.01 seconds, the amount of energy transferred to the material to be sintered is too small, resulting in a low sintering effect, and if the pulse of the extreme white light exceeds 10 seconds, the energy transferred to the material to be sintered is excessive, and the energy may reach the core-shell interface.
[0078] According to one embodiment, the pulse number of the extreme white light may be 1 to 30. In this specification, the pulse number refers to the number of times the extreme white light is repeatedly applied.
[0079] An excessive number of pulses exceeding 30 results in energy transfer to the core-shell interface and core material rather than partial sintering of the shell, which can have a negative effect similar to conventional thermal sintering.
[0081] According to one embodiment, the voltage applied to the light irradiation unit may be 100 V to 800 V. The voltage is related to the intensity of the extreme frequency white light.
[0082] If the voltage is less than 100 V, the light energy of the irradiated extreme white light is too weak and the shell cannot be sufficiently crystallized, and if the voltage exceeds 800 V, the intensity of the light energy of the irradiated extreme white light is too strong and unwanted chemical reactions may occur at the point where the core and the shell come into contact.
[0084] A core-shell structure comprising a selectively crystallized shell is manufactured according to the method for manufacturing a crystallinity-containing core-shell structure of the present invention.
[0085] Since extreme frequency white light is irradiated for a limited time of only a few seconds, only the shell in a core-shell structure can be partially photo-sintered, and crystallinity can be realized in the photo-sintered shell.
[0087] According to one embodiment, the thickness of the crystallized shell may be 10 nm to 50 μm. Preferably, the thickness of the crystallized shell may be 10 nm to 1 μm. More preferably, the thickness of the crystallized shell may be 14 nm to 16 nm.
[0088] The shell may naturally shrink during the cooling process following thermal sintering. However, in the case of photolithography, shell shrinkage hardly occurs due to the short process duration, so there is virtually no change in thickness before and after sintering.
[0090] According to one embodiment, the functional layer is photo-sintered and crystallized, and the crystallized shell has an ionic conductivity of 10 -12 S / cm to 10 -7 It can be S / cm.
[0091] Ionic conductivity is expressed in units as the reciprocal of resistance, so it is indicated through resistance measurements. Since amorphous solid materials before crystallization do not possess ionic conductivity, they have very large values in GΩ (giga-ohm) units when resistance is measured, and their reciprocal approaches zero, indicating ionic conductivity.
[0093] According to one embodiment, the core-shell structure may be included in any one selected from an all-solid-state battery, a lithium battery, and a fuel cell. That is, the core-shell structure having a crystalline shell may be used in various energy storage devices.
[0094] Taking lithium all-solid-state batteries as an example, unlike batteries using liquid electrolytes, interface control between the electrode active material and the electrolyte is critical. Specifically, the solid electrolyte and the electrode active material in an all-solid-state battery form a high-resistance film through chemical reactions at their contact surface. The formation of this film reduces the mobility of lithium ions between the solid electrolyte and the electrode active material, leading to a degradation in the performance of the lithium all-solid-state battery.
[0095] To solve this problem, a functional layer can be applied to prevent adverse reactions between the positive active material and the electrolyte in an energy storage device. In the core-shell structure according to the present invention, the core contains a positive active material, and the shell surrounding the core acts as a functional layer to prevent the adverse reaction; the core and the shell are collectively referred to as the positive material. That is, the photo-sintered shell can prevent contact between the electrolyte and the core, thereby preventing a reaction between the electrolyte and the positive active material.
[0096] In this specification, "side reaction" refers to an unintended reaction at the interface between two different materials. Side reactions involve the generation of new materials, resulting in the degradation or loss of function of energy storage devices, thereby reducing the quality of the finished product. Therefore, to minimize side reactions, there is currently a limitation in that materials must be selected restrictively, such as by choosing materials with high stability as active materials.
[0097] In this invention, without imposing limitations on the selection of materials, the light irradiation conditions of photo-sintering are controlled so that energy does not reach the interface between the shell and the core, thereby producing the effect of suppressing side reactions.
[0099] Cathode materials containing a core-shell structure are fabricated using non-vacuum wet chemical methods, or vacuum atomic layer deposition (ALD). When fabricating using the commonly used wet chemical methods, heat treatment is essential to facilitate reactions between compounds and the evaporation of organic matter. Since the functional layer is located between the electrolyte and the electrode active material, it serves as a pathway for lithium ion movement, requiring high ionic conductivity. Therefore, a heat treatment process is also necessary to achieve crystallinity for high ionic conductivity.
[0100] However, high-temperature, long-duration heat treatment through a sintering furnace entails issues such as long process time and cost, as well as the need to supply an excess amount of lithium ions due to the loss of lithium ions during sintering. In addition, when thermally sintering a core-shell structured cathode material containing a functional layer, there is a difficulty in performing the heat treatment to prevent adverse reactions between the cathode active material and the functional layer.
[0102] When a core-shell structured cathode material is photo-sintered using ultraviolet white light, the temperature of the core-shell tank can be raised within a few seconds, thereby reducing process time. Furthermore, by eliminating the need for lithium ion sublimation time, there is no need to use an excess amount of lithium ions, which has the effect of saving raw material costs. In addition, by performing photo-sintering instead of thermal sintering, the same effect as heat-treating only the functional layer portion of the cathode material can be achieved. As a result, the crystallinity and composition of the core cathode active material and the electrolyte are not affected, and unwanted interfacial reactions between the cathode active material and the functional layer do not occur, which can contribute to improving battery performance.
[0104] By using the photothermal sintering method according to one embodiment of the present invention, crystallization of only the shell can be induced in a core-shell structure without affecting the core, and the method for crystallizing a core-shell structure can be utilized in various fields.
[0106] [Comparative Example 1-1] Untreated
[0107] A core-shell structure was prepared using an ALD (Atomic Layer Deposition) machine, in which the core material was NCM (nickel-cobalt-manganese) and the shell material was LLTO (lithium lanthanum titanate). Sintering treatment was not performed.
[0109] [Comparative Example 1-2] Thermal Sintering Treatment
[0110] The core-shell structure of Comparative Example 1-1 was placed into a commercial electric furnace and heated to maintain 700°C.
[0112] [Example 1] Photothermal Sintering Treatment
[0113] A voltage of 600 V was applied to a xenon lamp to maintain a constant intensity of extreme white light, and the core-shell structure of Comparative Example 1-1 was irradiated.
[0114] The pulse was maintained for 10 seconds (actual light irradiation time; On-time) and the pulse gap (Off-time) was 500 seconds, and the irradiation was repeated 20 times (number of pulses).
[0116] [Comparative Example 2-1] Untreated battery
[0117] An all-solid-state lithium-ion battery (ASSLIB) was fabricated using a sulfide electrolyte, a Li foil anode, and the untreated NCM core-shell structure of Comparative Example 1-1 as the cathode. The battery was fabricated using a stacking method, with the Li foil placed at the bottom, the sulfide electrolyte stacked on top of it, and the cathode material stacked on top of that, and then fabricated by compression.
[0119] [Comparative Example 2-2] Thermal Sintering Battery
[0120] An all-solid-state lithium-ion battery was fabricated in the same manner as Comparative Example 2-1, except that the thermally sintered NCM core-shell structure of Comparative Example 1-2 was used as the cathode material.
[0122] [Example 2] Photo-sintered battery
[0123] An all-solid-state lithium-ion battery was fabricated in the same manner as Comparative Example 2-1, except that the NCM core-shell structure of Example 1, which was photo-sintered, was used as the cathode material.
[0125] Figure 2a shows a low-magnification TEM (Transmission Electron Microscope) image (left) and an EDS (Energy Dispersive X-ray Spectroscopy) image (right) of an untreated core-shell structure (Comparative Example 1-1). Figure 2b shows a low-magnification TEM (left) and EDS (Energy Dispersive X-ray Spectroscopy) image (right) of the untreated core-shell structure (Comparative Example 1-1) taken at a higher magnification than in Figure 2a. Referring to Figures 2a and 2b, the brightly glowing light green area represents the shell material; since it appears as a single color when it is a single material, it can be confirmed that the boundary between the shell and the core is clearly separated. This indicates that the shell was manufactured to be uniformly and well deposited onto the core material.
[0127] Figure 3a is an HR-TEM (high-magnification transmission electron microscope) image of an untreated core-shell structure (Comparative Example 1-1). Referring to Figure 3a, it can be seen that the shell portion of the core-shell structure has a thickness of 14 nm to 16 nm.
[0128] FIG. 3b is a high-magnification EDS (Energy Dispersive X-ray Spectroscopy) image of an untreated core-shell structure (Comparative Example 1-1). Referring to FIG. 3b, the respective materials constituting the shell and core parts can be identified. In the image, yellow represents the core part, purple represents the shell part, and green represents the material commonly contained in both the core and shell parts. Therefore, it can be confirmed that the material constituting the core is nickel (Ni) and oxygen (O) elements, and the material constituting the shell is zirconium (Zr) and oxygen (O) elements. FIG. 2a to FIG. 3b confirm that the core-shell structure was formed normally by ALD deposition.
[0130] Figure 4 is an image of a single particle constituting an untreated core-shell structure (Comparative Example 1-1) observed using SEM (Scanning Electron Microscope) and EDS (Energy Dispersive X-ray Spectroscopy). It can be seen that nickel (Ni), one of the materials constituting the core, and lanthanum (La) and titanium (Ti), which are LLTO materials constituting the shell, are evenly distributed on the powder surface.
[0132] Figure 5a is an HR-TEM image of a photo-sintered core-shell structure (Example 1). Referring to Figure 5a, it can be seen that the NCM constituting the core and the LLTO constituting the shell are in a state where crystallinity is expressed due to the rearrangement of the particle structures constituting each material. Crystallinity of the core was not expressed near the interface between the core and the shell.
[0134] Figure 5b is an image of a photo-sintered core-shell structure (Example 1). In Figure 5b, the area inside the yellow dotted line represents the core, and the area outside the yellow dotted line and inside the red dotted line represents the shell. At this time, the shell is in a crystalline state after photo-sintering. On the other hand, compared to the shell, no structural change occurred in the particles constituting the core material, indicating that the core was not crystallized. In other words, it was confirmed that a selective structural change occurred only in the shell portion during photo-sintering treatment.
[0136] Based on the crystallinity analysis results, whether the cation mixing effect between Li and Ni ions is suppressed after light irradiation is I 003 / I 104 It can be verified by the ratio. Cation mixing refers to a phenomenon in which ions with similar ionic radii exchange positions to form crystals. In NCM active materials, cation mixing results in Ni being positioned within the NCM layered structure, thereby eliminating sites where Li can enter. Consequently, NCM cathode materials in which cation mixing has occurred and sites for Li have disappeared experience a decrease in battery capacity and performance. Therefore, the cation mixing effect must be suppressed to maintain the layered structure and secure high capacity for the battery cathode material. The cation mixing effect can be suppressed by photosintering, and this is I 003 / I 104 It can be confirmed by the ratio of. I 003 / I 104 A high ratio means that cation mixing is well suppressed.
[0137] Figure 6 shows the results of crystallinity analysis performed on the examples and comparative examples using X-ray diffraction. Referring to Figure 6, the top blue graph is the graph of the core-shell structure (Example 1) treated with IPL photothermal sintering, and I 003 / I 104 The value is 1.345453. The red graph in the middle is the graph of the heat-sintered core-shell structure (Comparative Example 1-2), and I 003 / I 104 The value is 1.297883. The black graph at the bottom is the graph of the unprocessed core-shell structure (Comparative Example 1-1), and I 003 / I 104 The value is 1.376426. The unprocessed core-shell structure (Comparative Example 1-1) is the most ideal state, and therefore I 003 / I 104The value appears to be the highest, and cation mixing hardly occurs. When a post-processing step is performed to ensure the crystallinity of the shell in a core-shell structure, specific energy (heat, light) is required to secure crystallinity; therefore, additional energy is received compared to when sintering is not performed, creating an environment where cation mixing can occur. However, since photo-sintering has a much shorter process time compared to thermal sintering, it may have less influence on the cation mixing effect. In the thermally sintered core-shell structure (Comparative Example 1-2), cation mixing occurs actively, and I 003 / I 104 It was confirmed that the ratio decreased significantly, and I of the photo-sintered core-shell structure (Example 1) 003 / I 104 It was confirmed that the ratio decreased very slightly compared to the untreated core-shell structure (Comparative Example 1-1).
[0138] In addition, the clear appearance of peaks in the XRD graph indicates high crystallinity. When examining the (003) peak in Fig. 6, the graph of the core-shell structure (Example 1) that underwent photothermal sintering treatment, indicated in blue, shows the highest peak, which indicates the highest crystallinity. Therefore, when the core-shell structure is photothermally sintered using Example 1, the shell crystallizes, and cation mixing, which is one of the unwanted side reactions at the interface between the core and the shell, hardly occurs. Thus, it can be expected that when Example 1 is used as the cathode material for a battery, the performance of the battery will not deteriorate.
[0140] Figure 7 is a graph showing the charge / discharge capacity measured using the batteries of the example and comparative example.
[0141] The blue graph represents the core-shell structured battery treated with IPL photo-sintering (Example 2), the red graph represents the core-shell structured battery treated with thermal sintering (Comparative Example 2-2), and the black graph represents the untreated core-shell structured battery (Comparative Example 2-1). Referring to Fig. 7, it can be seen that the photo-sintered core-shell structured battery (Example 2) exhibits a high charge-discharge capacity similar to that of the untreated core-shell structured battery (Comparative Example 2-1). This suggests that the formation of the shell and the photo-sintering process do not have a negative effect on the core material, resulting in a capacity value comparable to that of the unsintered battery. On the other hand, it can be seen that the charge-discharge capacity of the thermally sintered core-shell structured battery (Comparative Example 2-2) is significantly reduced as thermal energy is transferred to the core during the process of applying heat. In the case of photo-sintering, the cation mixing effect was suppressed, increasing the crystallinity of the shell (functional layer); consequently, the ionic conductivity of the core-shell structure was enhanced, leading to an increase in charge-discharge capacity. In the case of thermal sintering, the crystallinity of the shell decreased due to the cation mixing effect, resulting in a decrease in charge-discharge capacity.
[0143] As described above, although the present invention has been explained by limited embodiments and drawings, the present invention is not limited to the above embodiments, and various modifications and variations are possible from this description by those skilled in the art to which the present invention belongs. Therefore, the scope of the present invention should not be limited to the described embodiments, but should be defined by the claims set forth below as well as equivalents thereof.
Claims
Claim 1 A method for manufacturing a core-shell structure comprising: a step of preparing a core-shell structure; and a step of selectively photo-sintering the shell by irradiating the core-shell structure with intense pulsed light (IPL) in a light irradiation unit, wherein the light irradiation conditions are controlled in the photo-sintering step so that energy does not reach the interface between the shell and the core. Claim 2 A method for manufacturing a crystalline core-shell structure according to claim 1, characterized in that, in the step of preparing the core-shell structure, the thickness of the shell is 10 nm to 50 μm. Claim 3 A method for manufacturing a core-shell structure according to claim 1, characterized in that, in the step of selectively photo-sintering the shell, the shell is selectively crystallized. Claim 4 A method for manufacturing a core-shell structure according to claim 1, characterized in that, in the step of selectively photo-sintering the shell, an interfacial reaction between the core and the shell is prevented. Claim 5 A method for manufacturing a core-shell structure according to claim 1, characterized in that the pulse of the extreme frequency white light is maintained for 0.01 seconds to 10 seconds. Claim 6 A method for manufacturing a core-shell structure according to claim 1, characterized in that the pulse number of the extreme frequency white light is 1 to 30. Claim 7 A method for manufacturing a core-shell structure according to claim 1, characterized in that the voltage applied to the light irradiation part is 100 V to 800 V. Claim 8 A core-shell structure manufactured according to claim 1 and optionally comprising a crystallized shell. Claim 9 A core-shell structure according to claim 8, characterized in that the thickness of the crystallized shell is 10 nm to 50 μm. Claim 10 In claim 8, the crystallized shell has an ionic conductivity of 10 -12 S / cm to 10 -7 A core-shell structure characterized by being S / cm. Claim 11 A core-shell structure according to claim 8, characterized in that the core-shell structure is included in any one selected from an all-solid-state battery, a lithium battery, and a fuel cell.
Citation Information
Patent Citations
Reduced graphene oxide-silicon metal particle composite formed by light irradiation, a method for producing the composite, and a electrode for secondary battery including the composite
KR1020190108731A
